The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11829-014-9319-y
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale spatial resource partitioning in a hyperparasitoid community

Abstract: International audiencePlant-herbivore-natural enemy associations underpin ecological communities, and such interactions may go up to four (or even more) trophic levels. Here, over the course of a growing season, we compared the diversity of secondary hyperparasitoids associated with a common host, Cotesia glomerata, a specialized larval endoparasi-toid of cabbage butterfly caterpillars that in turn feed on brassicaceous plants. Cocoon clusters of C. glomerata were pinned to ~30 Brassica nigra plants by pinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
1
24
2
Order By: Relevance
“…By contrast, G. agilis is wingless and can cover a smaller area per unit of time compared with A. nens. Wingless Gelis species appear to prefer searching for hosts on or close to the ground instead of in the canopy of forbs (Harvey et al, 2014;Heinen & Harvey, 2019). Honeydew excreted by aphids not only accumulates on leaf surfaces of the food plant, but also falls to the ground (Moller & Tilley, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, G. agilis is wingless and can cover a smaller area per unit of time compared with A. nens. Wingless Gelis species appear to prefer searching for hosts on or close to the ground instead of in the canopy of forbs (Harvey et al, 2014;Heinen & Harvey, 2019). Honeydew excreted by aphids not only accumulates on leaf surfaces of the food plant, but also falls to the ground (Moller & Tilley, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Niche partitioning often occurs on a temporal or spatial basis (Albrecht and Gotelli 2001;Harvey et al 2014;Moya-Raygoza et al 2012;Trizzino et al 2014;van Baaren et al 2004). Partitioning may occur on a relatively small scale, e.g., the height of a tree (Harvey et al 2014), or on a much larger scale such as elevation range (MoyaRaygoza et al 2012;Trizzino et al 2014). In parasitoids, coexistence may also be maintained by interspecific differences in various biological features related to host (common resource) exploitation, which might give each species an advantage over the others under specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several field studies have found that L. nana and A. nens frequently emerge from single cocoon clusters of C. glomerata in the field, strongly suggesting that they do compete for hosts (Poelman et al 2013, Harvey et al 2014, Zhu et al 2015. Furthermore, cocoons of C. glomerata remain suitable for parasitism for less than four days at 25°C (Harvey et al 2006), and this decreases rapidly under warmer conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Both species are idiobionts that attack non-growing host stages or prevent further host development and are largely specialized on cocoons of Cotesia species in nature, with C. glomerata appearing to be one of their more important hosts (Shwarz and Shaw 2000). The two hyperparasitoids appear to be bi-voltine and have very overlapping niches, both spatially and temporally (Harvey et al 2014). Several field studies have found that both species frequently emerge from single cocoon clusters of C. glomerata in the field, strongly suggesting that they do compete for hosts (Poelman et al 2013, Harvey et al 2014, Zhu et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation